Enveloppement – Bachelard et les philosophies de l’induction - Pravica, Sandra (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
The essay presents Bachelard’s philosophical assessment of mathematics for scientific thought in terms of his concept of induction and its successive modifications. In order to clarify the uniqueness of this view, I discuss it with positions on induction from the school of logical empiricism in the first half of the 20th century, which were formulated contemporaneously to Bachelard’s position. I contend that Bachelard keeps the concept relatable and develops the problem of induction progressively, while his contemporaries capitulate here by drawing philosophical boundaries. I first elaborate how Bachelard determines the activities of “discovery” and “emergence” in mathematics and in so doing brings “induction” into play. To outline the uniqueness of Bachelard’s concept of induction, I then sketch discussions of induction in the logical empiricism of the 1930s. In a final step, I show how Bachelard uses the term “induction” more and more idiomatically but in so doing opens the door to seeing the “problem” of iinduction as a new position in the philosophy of science.